Comparative pharmacokinetic study of dosage forms with morpholinium 2-[5-(pyridin-4-yl)-1,2,4-triazol-3-ylthio] acetate - I. V. Bushueva; V. V. Gladyshev; О. I. Panasenko; E. G. Knish (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Using mathematical models of income distribution and excretion of drugs greatly enhances the interpretation of the results of biopharmaceutical research. Pharmacokinetic modeling makes it possible to quantify the biological assessment of pharmaceutical factors, opens the possibility of a science-based regulation of the kinetics of substances introduced through targeted changesof pharmaceutical factors. Results of the study of kinetic models are used to solve some practical problems associated with pharmacological and clinical trials of medicines.